2018
DOI: 10.1017/ice.2018.312
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections following hip and knee arthroplastic surgery: Trends and risk factors of Staphylococcus aureus infections

Abstract: We investigated surgical site infections (SSIs) following hip and knee arthroplasties to evaluate predictors of SSI. We found a significant increase in deep Staphylococcus aureus (SA) SSIs despite the decreasing overall SSI rate. The risk of deep SA-SSI differed between genders and among age groups and was affected by timing of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
2
0
2
Order By: Relevance
“…The patient characteristics in the North control group were different as compared to those of the South group, in particular in terms of Altemeier classification, ASA scores, lengths of surgery, and proportion of surgical procedures for osteosyntheses, but North/South site variable was not included in the multivariate analysis because it did not modify the significance of the result. These results are coherent with those of literature; an analysis of 3,618 S. aureus SSI after knee and hip prosthesis procedures [ 31 ] found the following risk factors: male gender, length of surgery >120 minutes, ASA score ≥2 and hip prosthesis replacement. Diabetes, smoking, nasal carriage of S. aureus , cancer, the NNIS score and the BMI were also risk factors found in some orthopaedic surgery studies [ 9 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…The patient characteristics in the North control group were different as compared to those of the South group, in particular in terms of Altemeier classification, ASA scores, lengths of surgery, and proportion of surgical procedures for osteosyntheses, but North/South site variable was not included in the multivariate analysis because it did not modify the significance of the result. These results are coherent with those of literature; an analysis of 3,618 S. aureus SSI after knee and hip prosthesis procedures [ 31 ] found the following risk factors: male gender, length of surgery >120 minutes, ASA score ≥2 and hip prosthesis replacement. Diabetes, smoking, nasal carriage of S. aureus , cancer, the NNIS score and the BMI were also risk factors found in some orthopaedic surgery studies [ 9 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Periprosthetic joint infections still represent a challenge in medical practice, from early diagnosis, identification of causative pathogens, and proper management. 4,5 Although there are several clinical guidelines associated with the prevention of peri-and postoperative complications, it is observed that such normative divergence causes high rates of clinical variation in the management of patients undergoing hip arthroplasties, also resulting in different clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…As IAPs representam ainda um desafio na prática médica desde o seu diagnóstico precoce, identificação dos patógenos causadores e manejo adequado. 4,5 Embora existam diversas diretrizes clínicas associadas à prevenção de complicações peri-e pós-operatórias, observase que tal divergência normativa ocasiona altas taxas de variações no manejo de pacientes submetidos a artroplastias de quadril, resultando também em diferentes desfechos clínicos.…”
Section: Introductionunclassified
See 2 more Smart Citations